2005
DOI: 10.1128/jb.187.22.7703-7715.2005
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Analysis of Protein-Operator Interactions of the NikR and Fur Metal-Responsive Regulators of Coregulated Genes inHelicobacter pylori

Abstract: Two important metal-responsive regulators, NikR and Fur, are involved in nickel and iron homeostasis and controlling gene expression in Helicobacter pylori. To date, they have been implicated in the regulation of sets of overlapping genes. We have attempted here dissection of the molecular mechanisms involved in transcriptional regulation of the NikR and Fur proteins, and we investigated protein-promoter interactions of the regulators with known target genes. We show that H. pylori NikR is a tetrameric protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
213
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(232 citation statements)
references
References 37 publications
8
213
0
Order By: Relevance
“…The vast majority of these studies have focused on resistance to various stressful environments (10,18,27,60), identification of the regulon of genes controlled by each regulatory factor (16, 17, 19-21, 23, 61), or elucidation of the contribution of each regulator to colonization in an animal model (8)(9)(10)(11). Despite the evidence supporting the fact that the Fur, NikR, and ArsRS regulons show considerable overlap, very few studies (8,17,25,53) have attempted to analyze the combined effect of these regulatory factors in H. pylori biology. Herein, we constructed a series of isogenic regulatory knockout strains and evaluated H. pylori growth in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vast majority of these studies have focused on resistance to various stressful environments (10,18,27,60), identification of the regulon of genes controlled by each regulatory factor (16, 17, 19-21, 23, 61), or elucidation of the contribution of each regulator to colonization in an animal model (8)(9)(10)(11). Despite the evidence supporting the fact that the Fur, NikR, and ArsRS regulons show considerable overlap, very few studies (8,17,25,53) have attempted to analyze the combined effect of these regulatory factors in H. pylori biology. Herein, we constructed a series of isogenic regulatory knockout strains and evaluated H. pylori growth in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Examination of these transcriptome studies en masse demonstrates the vast and overlapping nature of the Fur, NikR, and ArsRS regulons. Furthermore, evidence suggests that these regulators affect expression of each other; nikR and arsR are part of the Fur regulon (23,24), whereas NikR appears to regulate fur (20,25). Given the overlapping nature of these regulatory cascades, it is likely not surprising that the role of each of these factors appears to be expanded compared to what is seen in other bacteria.…”
mentioning
confidence: 99%
“…In H. pylori, which requires the nickel enzyme urease to survive and colonize the acidic gastric mucus of the human stomach, NikR plays a more complex regulatory role. Transcriptome analysis of a deletion mutant and in vitro promoter-binding assays have revealed that H. pylori NikR (HpNikR) regulates transcription of not only the nickel importer and urease enzyme, but also other regulatory networks, some through repression of the gene encoding the ferric uptake regulator (Fur) protein (5)(6)(7)(8).…”
mentioning
confidence: 99%
“…in rich media, changes in gene expression are observed in response to Ļ³100 M) (6, 9 -11). From these studies, it appears that the recognition sequences in each promoter are defined by a series of poorly conserved 6-bp imperfect inverted repeat half-sites separated by a 15-bp spacer (5,7,12). HpNikR binds to these promoters with a range of affinities (5, 12).…”
mentioning
confidence: 99%